Impact of COVID-19 crisis on Energy Consumption and socio-spatial behavior of the residential sector in extreme climates. Case study Southwest of Algeria - Benoudjafer, Ibtissam; Benoudjafer, Imane; Laoufi, Salima (Technium Social Sciences Journal, 2022)
The outbreak of the COVID-19 pandemic has not only affected the health sector, but has affected all aspects of people’s lives, all economic, social and environmental sectors, including global energy. This article aims to study the impact of COVID 19 on the energy consumption of electricity, gas and water in the residential sector, where confinement has presented one of the associated measures taken by many countries to slow down. The objective of this article is to examine both the immediate and long-term impact of Covid-19 on energy consumption and on the socio-spatial behavior of occupants. The results show that there were variations in the domestic spatial spaces and a change in the social practices of each family. There is a sharp drop in the electricity consumption of single-family homes during the pandemic year. Other households have experienced an increase in electricity consumption during the summer months, mainly due to the periods of confinement such as travel restrictions imposed on the one hand and the harshness of the climate on the other. This study is essential for policymakers to detect changing patterns of electricity consumption in the context of emergencies such as the pandemic.